Pengaruh Antropometri Kit Menggunakan Stunting Early Detection Spinner (Sedpin) terhadap Status Pertumbuhan pada Anak Balita - Isra Nur Utari Syachnara Potabuga; Santoso Budi Rohayu (Universitas Malahayati Lampung, 2025)
ABSTRACT Globally, the prevalence of very short toddlers (stunting) in the South-East Asia region with the highest stunting prevalence rate (31.9%) in the world after Africa (33.1%) (World Health Organization, 2019). Indonesia is included in the countries in the South-East Asia region with a stunting prevalence rate of 36.4%. Based on data from the 2018 Basic Health Research (Riskesdas), the stunting rate in Indonesia was 30.8%. Based on the results of the Indonesian Nutritional Status Study (SSGI), the prevalence of stunting in toddlers was 24.4% in 2021, which means that almost a quarter of Indonesian toddlers experience stunting. To determine the Effect of the Anthropometric Kit using the Stunting Early Detection Spinner toward Growth Status in Toddlers. This type of research is a quantitative research with a Quasy Experiment with a Non-equivalent control group design with pre-test and post-test. The sampling technique was Purposive Sampling. The subjects of the study were toddlers in the Fakfak Fakfak City Health Center Working Area. This type of research is a quantitative research with a Quasy Experiment with a Non-equivalent control group design with pre-test and post-test. The sampling technique was Purposive Sampling. The subjects of the study were toddlers in working area of Fakfak Public Health Center. There is escalation of Mean value of Growth Status and there are a significant difference (p0.05) after being given Stunting Early Detection Spinner on the intervention group. There is no escalation in the Mean value Growth Status and there was no difference (p0.05) in growth status in the control group. There is a significant difference (p0.05) in the difference in growth status scores in the intervention and control groups. Stunting Early Detection Spinner is a variable that is closely related to growth status (p0.05). There is an effect of the Anthropometry Kit using the Stunting Early Detection Spinner (SEDPIN) on Growth Status on Toddlers Keywords: Anthropometry, Toddler, Stunting, Early Detection ABSTRAK Secara global, prevalensi pada balita sangat pendek (stunting) di wilayah South-East Asia dengan angka prevalensi stunting yang tertinggi (31,9%) di dunia setelah Afrika (33,1%) (World Health Organization, 2019). Indonesia termasuk ke dalam negara di wilayah South-East Asia dengan angka prevalensi stunting sebesar 36,4%. Berdasarkan data hasil Riset Kesehatan Dasar (Riskesdas) tahun 2018, angka stunting di Indonesia sebesar 30,8%. Berdasarkan hasil Studi Status Gizi Indonesia (SSGI) prevalensi Balita stunting sebesar 24,4% pada 2021 yang artinya, hampir seperempat Balita Indonesia mengalami stunting. untuk mengetahui Pengaruh Antropometri Kit menggunakan Stunting Early Detection Spinner terhadap Status Pertumbuhan Pada Anak Balita. Jenis penelitian ini adalah penelitian kuantitatif dengan Quasy Experiment dengan desain Non–equivalen control group with pre test and post test. Teknik pengambilan sampel dengan Purposive Sampling. Subjek penelitian adalah Balita di Wilayah Kerja Puskesmas Fakfak Fakfak Kota.Terdapat peningkatan nilai Mean Status Pertumbuhan dan terdapat perbedaan bermakna yang signifikan (p0,05) setelah diberi Stunting Early Detection Spinner pada kelompok intervensi. Tidak ada peningkatan nilai Mean Status Pertumbuhan dan tidak terdapat perbedaan (p0,05) status pertumbuhan pada kelompok kontrol. Terdapat perbedaan bermakna (p0,05) selisih skor status pertumbuhan pada kelompok intervensi dan kontrol. Stunting Early Detection Spinner merupakan variabel yang erat hubungnya berpengaruh terhadap status pertumbuhan (p0,05). Ada pengaruh Antropometri Kit menggunakan Stunting Early Detection Spinner (SEDPIN) terhadap Status Pertumbuhan Pada Anak Balita Kata kunci: Antropometri, Balita, Stunting, Deteksi Dini